Design Training and Creativity: Students Develop Stronger Divergent but Not Convergent Thinking - Xia, Tiansheng; Kang, Mengxia; Chen, Meng; Ouyang, Jia; Hu, Fei (Frontiers in Psychology, 2021)
Design training programs that teach creativity often emphasize divergent thinking (generation of ideas) more than convergent thinking (evaluation of ideas). We hypothesized that training would lead to more both types of creativity, but especially divergent thinking. Three groups of university students (N = 120; n = 40 in each group) were recruited to participate: senior design students (graduate students with at least four years of design training as undergraduates); junior design students (undergraduates in their first year of design training); undergraduate students in majors unrelated to design. The students completed three tasks in a classroom setting to assess divergent thinking (Alternate Uses Task), convergent thinking (Remote Associates Task), and nonverbal abstract reasoning (Raven’s Progressive Matrices Test). The results of one-way ANOVAs showed that as expected, senior design students significantly outperformed junior design students and non-design majors in divergent thinking. However, contrary to expectations, senior design students had significantly lower scores than the non-design group on convergent thinking; the junior design students' scores fell in the middle but were not significantly different from either of the other groups. There were no group differences in nonverbal abstract reasoning. These findings suggest that design training significantly improves students’ ability to generate ideas, but does not improve, or may even hinder, their ability to evaluate whether the ideas are useful for the task at hand. The results have implications for developing a research-based curriculum in design training programs.